(untitled) (Acta Polytechnica CTU Proceedings, 2022)
Building performance simulation serves the derivation of the relevant building performance indicators (e.g., energy use, indoor-environmental conditions) given the assumptions of certain model input parameters (i.e., description of the building, boundary conditions, occupants’ presence and behaviour). Simulation can be employed for multiple purposes, including but not limited to building design support, building systems configuration, and code compliance demonstration. It has been suggested that the level of detail and resolution of simulation models must match their deployment purpose. However, there is arguably a lack of definitive guidelines for the purpose-dependent selection of appropriate simulation models. To address this challenge, the present contribution suggests that the attributes of a simulation model in general, and the type of the adopted occupant model in particular, must correspond to the specifics of the building performance indicator under investigation. To make progress in this area, a typological classification of building performance indicators is proposed along three salient dimensions, namely the indicators’ topical domain (e.g., energy use, thermal comfort, noise control), their spatial attributes, and their temporal attributes. Following a detailed analysis, the paper presents a high-level approach to derive the basic requirements concerning occupant models as a categorical function of the simulation purpose.